Recyclable and Dual Cross‐Linked High‐Performance Polymer with an Amplified Strength–Toughness Combination. Issue 5 (31st January 2020) - Du, Mengqi; Yang, Li; Liao, Cong; Diangha, Tasah Philas; Ma, Yuanchi; Zhang, Lin; Lan, Yang; Chang, Guanjun
Abstract: Supramolecular chemistry has provided versatile and affordable solutions for the design of tough, flexible polymers. However, application of supramolecular chemistry has been limited to the production of rigid, high‐performance polymers due to weak segment mobility. This paper describes a new method of toughening rigid high‐performance polymers using the synergistic effect between dual Cu 2+ ‐coordination bonds as a crosslink. These dual Cu 2+ ‐coordination cross‐linked high‐performance polymers are a class of rigid polymers with an outstanding combination of strength and toughness. The distinct lifetimes and binding strengths of the dual Cu 2+ ‐coordination bonds in a rigid polymer network elicit different dynamic behaviors to improve its energy dissipation and mechanical properties. Moreover, the reformation and removal of Cu 2+ ‐coordination bonds by pyrophosphoric acid endows these cross‐linked high‐performance polymers with recyclability. Abstract : A new method of toughening rigid high‐performance polymers is proposed to improve its energy dissipation and mechanical properties using the synergistic effect between dual Cu 2+ ‐coordination bonds as a crosslink with distinct lifetimes and binding strengths. Moreover, the reformation and removal of Cu 2+ ‐coordination bonds by pyrophosphoric acid endows these cross‐linked high‐performance polymers with recyclability.